1995
DOI: 10.1126/science.7846531
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Roles for Receptor Occupancy and Aggregation in Integrin Transmembrane Function

Abstract: Integrin receptors mediate cell adhesion, signal transduction, and cytoskeletal organization. How a single transmembrane receptor can fulfill multiple functions was clarified by comparing roles of receptor occupancy and aggregation. Integrin occupancy by monovalent ligand induced receptor redistribution, but minimal tyrosine phosphorylation signaling or cytoskeletal protein redistribution. Aggregation of integrins by noninhibitory monoclonal antibodies on beads induced intracellular accumulations of pp125FAK a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
555
1
10

Year Published

1996
1996
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 825 publications
(593 citation statements)
references
References 26 publications
27
555
1
10
Order By: Relevance
“…[9,129,[216][217][218] In this way, a study addressing the mechanism by which T cell responses are enhanced by the co-receptor CD28 was undertaken. [87] Ligand binding to the TCR is necessary and sufficient for activation of T cells; however, co-stimulation of CD28 yields a more potent response.…”
Section: 1b G-protein Coupled Receptors (Gpcrs)-gpcrsmentioning
confidence: 99%
“…[9,129,[216][217][218] In this way, a study addressing the mechanism by which T cell responses are enhanced by the co-receptor CD28 was undertaken. [87] Ligand binding to the TCR is necessary and sufficient for activation of T cells; however, co-stimulation of CD28 yields a more potent response.…”
Section: 1b G-protein Coupled Receptors (Gpcrs)-gpcrsmentioning
confidence: 99%
“…Dimerization is a well-known mechanism for activation of receptor kinases [62]. Intramembrane clustering has also been shown to be important for activation of downstream activities of non-catalytic receptors [63,64] and cell-adhesion molecules [65][66][67][68].…”
Section: Core-protein-mediated Oligomerizationmentioning
confidence: 99%
“…Integrin receptors bind talin [133] and α-actinin [134] and other cytoskeleton-associated proteins [65,68,117], selectins bind α-actinin [135], and cadherins bind catenins [136]. In the case of integrin receptors it has been shown that one of the elements that regulates cytoskeleton association is clustering of the receptors within the plane of the membrane [65].…”
Section: Syndecan-cytoskeleton Associationmentioning
confidence: 99%
See 1 more Smart Citation
“…A prominent example is the transport of oosperm from ovary to uterus through the fallopian tube during pregnancy. While it is clear that the transport of oosperm involves smooth muscle contraction [1,2], the detailed mechanism still remains elusive [1][2][3][4][5][6][7], due in part to the complexity of cellsubstrate interactions via receptor-ligand binding as well as various physical forces inside and outside of the cytoskeleton [8][9][10][11][12]. Cells are known to respond to mechanical forces exerted through surrounding fluid, adhering beads or substrates [9,[12][13][14], and they could detach, slip or roll on a substrate in response to these forces [15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%